Vers une caractérisation synthétique des régimes monétaires en économie capitaliste : conceptualisation et jalons pour une application au cas du régime monétaire européen - Vittorio Mazzotta (Revue de la Régulation)
We propose in this paper a synthetic definition of monetary regimes for a capitalist economy derived from the principal research of the regulation theory on that matter. We arrive at a synthetic characterization of a monetary regime articulated in two layers: the first constituting the institutional frame regulating the conflict between industrial capital and financial capital and the second corresponding to a freedom space useful to the regime to reproduce itself in normal times and maintain its state in time of crisis. We will apply this framework to the Eurozone and will show that the financial capital has always the advantage over the industrial capital and that the financial capital takes mostly the form of fictitious capital. We will later analyze the role of monetary policy and financial regulation in this context. We find that monetary and financial policy is always conducted in coherence with that state of the balance of power between industrial and financial capital.